STRATEGI PENGEMBANGAN UNIT PENGELOLAAN SAMPAH NON ORGANIK - Sarah, Sarah; Iskandar, Abubakar; Subagdja, R. Oetje; Wahyudin, Cecep (Administratie: Jurnal Administrasi Publik, 2021)
Maintaining, managing, and protecting the environment's cleanliness, especially those arising from waste is not easy, littering means removing trash, wrongly means removing. The research aims to sort out inorganic waste according to its type, to explain the application of reducing landfill waste, managing it so that it doesn’t become garbage and reuse management results through the Waste Bank. Quantitative qualitative methods. Direct data/not good observation, interview, documentation. Sampling 40 people. Flow Model Analysis, Product Moment Correlation, and Community Perception Analysis. Some conclusions: the value of r = 0.421 means that the relationship between inorganic waste management and the waste bank is very close, and 0.513 means that the relationship between type of inorganic waste and the socialisation of the waste bank is very close. 0.356 means that the relationship between types of inorganic waste and waste banks is quite close. 0.634 means that the relationship between the types of inorganic waste and inorganic waste management is very close. 0.363 means that the income value of inorganic waste and types of inorganic waste is quite close, value of 368 means the relationship between the income value of inorganic waste and management of inorganic waste is quite close.